Biologically inert ceramics thermodynamic mechanisms and models in cutting and grinding: a comparative assessment - Xianggang Kong; Xiaotong Chen; Min Yang; Fuhe Hao; Xin Cui; Mingzheng Liu; Benkai Li; Yanbin Zhang; Xiao Ma; Changhe Li (Journal of Materials Research and Technology)
Biologically inert ceramics are commonly employed in bone replacement surgeries because of their outstanding biocompatibility and exceptional mechanical properties. Grinding is an essential processing step for biologically inert ceramics prior to clinical application. However, the inherent properties of biologically inert ceramics, including high hardness, brittleness, and low thermal conductivity, make them susceptible to both thermal and mechanical damage during the process of cutting and grinding. Therefore, establishing predictive models for cutting and grinding forces, as well as temperature, during the machining process are important. However, current research on predictive models for the cutting and grinding force and temperature of various inert ceramics is relatively scarce, and there is a lack of corresponding reviews to provide unified guidance. Based on this, this paper summarizes the cutting and grinding force mechanisms and cutting and grinding heat models for different types of biologically inert ceramics during the cutting and grinding process. First, based on the different types of ceramics, this paper summarizes the grinding force models for each type of biologically inert ceramic material under various grinding and milling processes, along with the accuracy errors associated with each model. Subsequently, the cutting and grinding temperature models of various ceramic materials and the accuracy errors of each model are summarized. Additionally, it reviews the applications of these grinding force and temperature models, revealing the effect of processing parameters on grinding force and temperature during the process of machining. At the same time, an optimization analysis of the machining parameters in cutting and grinding processes was conducted, and the optimal range of machining parameters under different processing methods was determined. Finally, in light of the current challenges in the grinding of biologically inert ceramic materials, this paper proposes possible future research directions aimed at providing theoretical guidance and technical support to enhance the processing quality of workpieces during the grinding of biologically inert ceramics.